Corrigendum to “Electrospinning of recombinant human-like collagen-reinforced PCL nanofibrous membranes using benign solvents for periodontal regeneration” [Int. J. Biol. Macromol. 284 (Part 1) (January 2025) 137954](S0141813024087658)(10.1016/j.ijbiomac.2024.137954) - Ren, Minyi; Li, Meng; Boccaccini, Aldo R.; Xu, Yan; Li, Lu; Zheng, Kai (International Journal of Biological Macromolecules, 2025)
The authors regret that the affiliations of Minyi Ren, Yan Xu, Lu Li, and Kai Zheng should be corrected as follows: From: aJiangsu Province Engineering Research Center of Stomatological Translational Medicine, Nanjing, 210029, China bDepartment of Periodontology, The Affiliated Stomatological Hospital of Nanjing Medical University, Nanjing, 210029, China cState Key Laboratory Cultivation Base of Research, Prevention and Treatment for Oral Diseases, Nanjing, 210029, ChinaTo: aDepartment of Periodontics, The Affiliated Stomatological Hospital of Nanjing Medical University, Nanjing, 210029, China bJiangsu Province Engineering Research Center of Stomatological Translational Medicine, Nanjing Medical University, Nanjing, 210029, China cState Key Laboratory Cultivation Base of Research, Prevention and Treatment for Oral Diseases, Nanjing Medical University, Nanjing, 210029, ChinaThe authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2025-07-04